Description of the Widyaiswara Credibility in Learning Communication at Balai Pendidikan dan Pelatihan Keagamaan Padang - Rahmat Fahmi; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
The research was motivated by the success of participant in training program at learning and training religious center Padang, this is may cause by credibility of widyaiswara in learning communication. The aim of this study is to see the credibility widyaiswara in learning communication seen from the aspect of ethos, pathos, and logos. This research is descriptive quantitative research. The population sample of this research is the participant of training at at learning and training religious center Padang amount of 30 participants. The technique of this research is cluster random sampling, the sample that is taken about 15 participants. The data collection technique is by questionnaire. While the data collection tool is questionnaire sheet. The data analysis technique by percentage formula. The research found that (1) the credibility of widyaiswara in learning communication seen ethos aspect is very credible, (2) the credibility of widyaiswara in learning communication seen pathos aspect is very credible, (3) the credibility of widyaiswara in learning communication seen logos aspect is very credible.Keywords: Widyaiswara, Credible, Communication Learning